LEGAL REGIME OF DRUG TRAFFIC: STAGES IN THE DEVELOPMENT OF LEGISLATION AND THE ROLE OF CONTROL RELATIONS - Shevchuk, Oleksandr; Bululukov , Oleg; Maryniv, Ivanna; Shevchuk, Anatolii (Revista Inclusiones, 2020)
In this article, various interconnections and patterns of the development of control of legal relations and the legislation on drugs were studied (during the period from XI to 1936). Important basic elements in this study are following: general scientific and special scientific techniques and methods as abstraction, generalization, comparative historical, comparative legal, systemic, logical form. The use of the historical and legal method made it possible to trace the genesis of scientific approaches to the formation of control of legal relations between drugs and legislation in Ukraine, and to periodize the stages of its formation. The retrospective of the emergence, formation and development of control of legal relations regarding drugs and control organisations is analyzed, at different times they were responsible for the practical implementation of anti-drug activities. The aforementioned made it possible to justify the allocation of three main stages, each of which is associated with certain key events, political or social phenomena, changes and restructures of the entire state administration, namely: XI century - beginning of the XX century; 1909-1916, 1917 - 1936. Studying the stages of development of control of relations and anti-drug legislation will allow us the opportunity to offer effective ways to improve it in modern conditions.